Neuromuscular and technical abilities related to age in water-polo players - De Siati, F.; Laffaye, G.; Gatta, G.; Dello Lacono, A.; Ardigò, L. P.; Padulo, J. (Journal of Sports Sciences, 2016)
Testing is one of the important tasks in any multi-step sport programme. In most ball games, coaches assess motor, physical and technical skills on a regular basis in early stages of talent identification in order to further athletes` development. The purpose of the study was to investigate anthropometric variables and vertical jump heights as a free throw effectiveness predictor in water-polo players of different age groups. Two hundred and thirty-six young (10-18 years) male water-polo players partitioned into three age groups underwent anthropometric variables` measures and squat- and countermovement-jump tests, and performed water-polo free throws. Anthropometric variables, vertical jump heights and throw speed - as a proxy for free throw effectiveness - resulted different over age groups. Particularly, throw speed changed from 9.28 to 13.70 m/s (+48%) from younger to older players. A multiple-regression model indicated that body height, squat-jump height and throw time together explain 52% of variance of throw speed. In conclusion, tall height, high lower limb power and throwing quickness appeared to be relevant determinants for effective free throws. Such indications can help coaches during talent identification and development processes, even by means of novel training strategies. Further research is needed over different maturity statuses.